Richard Batka's Relationship to Personalities of Czech Music - Koptova, Marketa (Musicologica Olomucensia, 2012)
At the turn of the 20th century, Czech and German cultures encountered each other in Prague, which often led to controversies and personal disputes. A music critic, librettist, theoretician and organizer, Richard Batka (1868-1922) was of German origin. He collaborated with the director of the New German Theatre, Angelo Neumann, supported cultural life in Prague, organized lecturing, concerts and exhibitions. It was at his instigation that Richard Strauss and Anton Bruckner visited Prague. As a spokesman of the German musical culture in Prague, Batka often found himself in conflict with the Czech cultural scene, for example when he criticized Karel Burian' performance in the opera Salome by Richard Strauss. Batka's The history of Czech Music became in turn the object of criticism of Zdenek Nejedly's article ``Richard Batka uber die cechische Musik''.
Keywords: Richard Batka; Karel Burian; Zdenek Nejedly; criticism; opera; history of music